2018
DOI: 10.1177/1359105318782375
|View full text |Cite
|
Sign up to set email alerts
|

Depressive symptoms prospectively predict cardiovascular disease among older adults: Findings from the Maine-Syracuse Longitudinal Study

Abstract: A recent meta-analysis identified a prospective association between depression and cardiovascular disease; however, there was no association for studies with long-term follow-up periods. The literature has primarily focused on baseline depression status or symptoms, which may not capture the chronic nature of depression. This study examined the prospective relationship between depressive symptoms and cardiovascular disease up to 15 years later in 274 cardiovascular disease-free older adults. Depressive and anx… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 24 publications
0
4
0
Order By: Relevance
“…The presence of depressive symptoms was a negative influencing factor for subjective well-being. Depressive symptoms had been proved to be associated with functional limitation ( Hairi et al., 2011 ), mortality ( Correa et al., 2021 ), and cardiovascular disease ( Haigh et al., 2020 ). In addition, because of generating more negative emotions and relating to avoidant coping ( Thimm et al., 2018 ), depressive symptoms exert a negative impact on subjective well-being.…”
Section: Discussionmentioning
confidence: 99%
“…The presence of depressive symptoms was a negative influencing factor for subjective well-being. Depressive symptoms had been proved to be associated with functional limitation ( Hairi et al., 2011 ), mortality ( Correa et al., 2021 ), and cardiovascular disease ( Haigh et al., 2020 ). In addition, because of generating more negative emotions and relating to avoidant coping ( Thimm et al., 2018 ), depressive symptoms exert a negative impact on subjective well-being.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have demonstrated that basic demographic characteristics, including sex, age, marital status, educational level, and residence, are associated with depressive symptoms in older Chinese populations [ 7 , 19 ]. Moreover, physical health status, especially chronic diseases, is closely related to depressive symptoms in older adults [ 20 22 ]. Accordingly, we collected demographic information and the number of chronic diseases suffered by the participants to investigate how these variables influenced the latent growth trajectories of depressive symptoms over time in the older Chinese population.…”
Section: Methodsmentioning
confidence: 99%
“…Depression is associated with a greater risk of cardiovascular mortality in older adults (18,19). There is also an increased risk of coronary heart disease in depressive disorders (20)(21)(22). Even mild depression has a higher risk of CVD, which is greater amongst those with chronic or recurrent depression (20).…”
Section: Introductionmentioning
confidence: 99%
“…There is also an increased risk of coronary heart disease in depressive disorders (20)(21)(22). Even mild depression has a higher risk of CVD, which is greater amongst those with chronic or recurrent depression (20). Furthermore, there is an increased risk of stroke and cardiovascular related mortality in older people with depression and comorbid hypertension (23,24).…”
Section: Introductionmentioning
confidence: 99%